Synthesis and oxidation of some azole-containing thioethers; Beilstein Journal of Organic Chemistry; Vol. 7 - Potapov A. S. Andrey Sergeevich; Chernova N. P.; Ogorodnikov V. D.; Petrenko T. V.; Khlebnikov A. I. Andrey Ivanovich (2011, 2011)
Title screen